Strategies for Promoting Social Justice in the Math Classroom - Panthi, Ram Krishna; Luitel, Bal Chandra; Belbase, Shashidhar (Universitas Ahmad Dahlan, 2018)
The purpose of this paper is to discuss the strategies used by the teachers for promoting social justice in the math classroom. An interpretive qualitative research method was applied for data construction, analysis and interpretation through an iterative process. Three math teachers and their three students (one for each teacher) were selected as the research participants purposively from three public secondary schools in Kathmandu. Qualitative narratives were generated through in-depth interviews and classroom observations with each participant. The data analysis went through multiple layers of thematic analyses and interpretations of the narratives from the interview data. Altogether six themes emerged from the analysis of the data. These themes include–counseling and encouragement, group work and cooperative learning, linking mathematics to daily life, personalized way of instruction, promotion of joyful environment, and class work and projects.